Beyond the Game: The Influence of Varying Degrees of Sports Involvement on College Students’ Self-Perceptions and Institutional Affiliation - Dalit Lev Arey; Orr Levental (Education Sciences, 2024)
This research investigates the impact of varying levels of sports participation on college students’ self-perception and their sense of connection to their educational institution, with a specific focus on an Israeli context. Recognizing the gap in the existing literature regarding the nuanced effects of different degrees of sports engagement, this study aims to offer insights into how sports involvement shapes students’ academic, social, and psychological experiences. Utilizing a qualitative approach, the research involved conducting 26 semi-structured interviews with undergraduate students from a northern Israeli college, encompassing a diverse range of sports participation levels, from occasional involvement to committed varsity athletes. The findings reveal that sports participation significantly enhances students’ perceptions of their academic and social abilities, fosters a sense of belonging to the institution, and cultivates institutional pride, regardless of the level of involvement. Particularly noteworthy is the positive correlation between sports engagement and heightened self-esteem and self-efficacy. This study contributes to the understanding of the broader impacts of sports in higher education, highlighting its role in personal development and institutional affiliation. The research underscores the need for further studies in varied cultural contexts to deepen the understanding of these dynamics. Additionally, the study’s focus on an Israeli sample provides a unique perspective on the role of sports in a culture where collegiate sports are less academically explored. This research serves as a stepping stone for future quantitative investigations to objectively measure and enhance the understanding of the relationship between sports participation and student development in higher education.